A micropatterned thermoplasmonic substrate for neuromodulation of in vitro neuronal networks. (1st March 2023) - Andolfi, Andrea; Arnaldi, Pietro; Lisa, Donatella Di; Pepe, Sara; Frega, Monica; Fassio, Anna; Lagazzo, Alberto; Martinoia, Sergio; Pastorino, Laura
Abstract: Understanding how the spatial organization of a neural network affects its activity represents a leading issue in neuroscience. Thanks to their accessibility and easy handling, in vitro studies remain an essential tool to investigate the relationship between the structure and function of a neuronal network. Among all the patterning techniques, ink-jet printing acquired great interest thanks to its direct-write approach, which allows the patterned substrate realization without mold, leading to a considerable saving of both cost and time. However, the inks commonly used give the possibility to control only the structure of a neuronal network, leaving aside the functional aspect. In this work, we synthesize a photosensitive ink combining the rheological and bioadhesive properties of chitosan with the plasmonic properties of gold nanorods, obtaining an ink able to control both the spatial organization of a two-dimensional neuronal network and its activity through photothermal effect. After the ink characterization, we demonstrate that it is possible to print, with high precision, different geometries on a microelectrode array. In this way, it is possible obtaining a patterned device to control the structure of a neuronal network, to record its activity and to modulate it via photothermal effect. Finally, to our knowledge, we report the first evidence of photothermal inhibition of human neurons activity. Statement of significance: Patterned cell cultures remain the most efficient and simple tool for linking structural and functional studies, especially in the neuronal field. Ink-jet printing is the technique with which it is possible to realize patterned structures in the fastest, simple, versatile and low-cost way. However, the inks currently used permit the control only of the neuronal network structure but do not allow the control-modulation of the network activity. In this study, we realize and characterize a photosensitive bioink with which it is possible to drive both the structure and the activity of a neuronal network. Moreover, we report the first evidence of activity inhibition by the photothermal effect on human neurons as far as we know. Graphical abstract: Image, graphical abstract